ANALISIS PH, KEKERUHAN DAN JARAK AIR BERSIH TERHADAP SISA KLOR PADA JARINGAN DISTRIBUSI PELANGGAN IPA 1 A.YANI PTAM BANDARMASIH ZONA BANJARMASIN BARAT - Ramadhani, Nadila Rusma; Alim, Muhammad Syahirul Alim; Husin, Muhammad; Firdausy, Muhammad Abrar (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Water is one of the crucial factors determining the basic needs of human life on Earth. The increasing demand for drinking water, if not accompanied by an increase in its production capacity, can lead to issues in service provision. PTAM Bandarmasih is a government institution responsible for providing clean water for the residents of Banjarmasin city. The objective of this research is to analyze the pH, turbidity, and distance of clean water related to residual chlorine in the distribution pipeline network within the customers' houses in IPA 1 A.Yani PTAM Bandarmasih Zone West Banjarmasin. This study is an analytical observational research using survey methods. A total of 30 water quality samples were taken from different locations, each representing a District Meter Area (DMA) block in the West Banjarmasin Zone. The data analysis employed univariate and bivariate analyses using Pearson correlation and Spearman Rank correlation. This method involved measuring all relevant variables and then conducting statistical analysis to observe the relationships between these variables. The research findings indicate that the average pH in the distribution water of IPA 1 A.Yani PTAM Bandarmasih is 7, with an average turbidity of 3.41 NTU. The average distance between customers' houses and IPA 1 A.Yani is 4.7 km. The analysis reveals strong correlations: pH with a correlation of -0.767, turbidity with a correlation of -0.779. The parameter most strongly related to residual chlorine value is the distance, with a very strong correlation of -0.850.